Is dairy consumption associated with low cardiovascular disease risk in European adolescents? Results from the HELENA Study. Issue 5 (15th July 2013) - Bel‐Serrat, S.; Mouratidou, T.; Jiménez‐Pavón, D.; Huybrechts, I.; Cuenca‐García, M.; Mistura, L.; Gottrand, F.; González‐Gross, M.; Dallongeville, J; Kafatos, A.; Manios, Y.; Stehle, P.; et al.
Summary What is already known about this subject Although there is no clear evidence of the role of dairy consumption on cardiovascular disease (CVD) risk development in adults, several studies have suggested dairy consumption to have a protective effect. Limited evidence on the relationship between milk and dairy products consumption and CVD risk factors among adolescents. What this study adds Dairy consumption was inversely associated with CVD risk in European adolescent girls. Higher dairy consumption was associated with lower adiposity and higher cardiorespiratory fitness in both genders. Objective To identify those food groups best discriminating individuals at high/low cardiovascular disease (CVD) risk and to investigate the relationship between dairy consumption and CVD risk factors (individual and scores) in adolescents (12.5–17.5 years) from eight European cities participating in the cross‐sectional (2006–2007) HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) project. Methods Diet, waist circumference, skin‐folds thickness, systolic blood pressure, insulin resistance, triglycerides, total cholesterol/high‐density lipoprotein ratio and cardiorespiratory fitness (CRF) were assessed in 511 (49.9% boys) adolescents. Individual z‐scores of CVD risk factors were summed to compute sex‐specific clustered CVD risk scores. Results Dairy emerged as the food group best discriminating adolescents at low/high CVD risk. In both genders, waist circumference and sum of skin‐folds were inversely associated with consumption of milk and yogurt, and milk‐ and yogurt‐based beverages, whereas a positive association was observed with CRF. Moreover, CVD risk score (β = −0.230, P = 0.001) was also inversely associated with overall dairy consumption only in girls. Discussion Dairy consumption is associated with lower adiposity and higher CRF in these adolescents. An inverse association between CVD risk score and dairy consumption is also depicted in girls. The study adds further evidence to the scarce literature on the influence of milk and dairy products on adolescents' cardiovascular health.